General practitioners' perspectives on the prevention of cardiovascular disease: systematic review and thematic synthesis of qualitative studies. Issue 11 (1st November 2018) - Ju, Irene; Banks, Emily; Calabria, Bianca; Ju, Angela; Agostino, Jason; Korda, Rosemary J; Usherwood, Tim; Manera, Karine; Hanson, Camilla S; Craig, Jonathan C; Tong, Allison
Abstract : Objective: Cardiovascular disease (CVD) is a leading cause of morbidity and mortality globally, and prevention of CVD is a public health priority. This paper aims to describe the perspectives of general practitioners (GPs) on the prevention of CVD across different contexts. Design: Systematic review and thematic synthesis of qualitative studies using the Enhancing Transparency of Reporting the Synthesis of Qualitative research (ENTREQ) framework. Data sources: MEDLINE, Embase, PsycINFO and CINAHL from database inception to April 2018. Eligibility criteria for selecting studies: We included qualitative studies on the perspectives of GPs on CVD prevention. Data extraction and synthesis: We used HyperRESEARCH to code the primary papers and identified themes. Results: We selected 34 studies involving 1223 participants across nine countries. We identified six themes: defining own primary role (duty to prescribe medication, refraining from risking patients' lives, mediating between patients and specialists, delegating responsibility to patients, providing holistic care); trusting external expertise (depending on credible evidence and opinion, entrusting care to other health professionals, integrating into patient context); motivating behavioural change for prevention (highlighting tangible improvements, negotiating patient acceptance, enabling autonomy and empowerment, harnessing the power of fear, disappointment with futility of advice); recognising and accepting patient capacities (ascertaining patient's drive for lifestyle change, conceding to ingrained habits, prioritising urgent comorbidities, tailoring to patient environment and literacy); avoiding overmedicalisation (averting long-term dependence on medications, preventing a false sense of security, minimising stress of sickness) and minimising economic burdens (avoiding unjustified costs to patients, delivering practice within budget, alleviating healthcare expenses). Conclusions: GPs sought to empower patients to prevent CVD, but consideration of patients' individual factors was challenging. Community-based strategies for assessing CVD risk involving other health professionals, and decision aids that address the individuality of the patient's health and environment, may support GPs in their decisions regarding CVD prevention.